Conscious Conception: A Qualitative Study of Intentional Prenatal Engagement and Parental Experience - Abhishek Pasari; Dhruthi Prasad (Journal of Prenatal and Perinatal Psychology and Health, 2026)
This study explores the concept of Conscious Conception as a form of intentional psychological engagement during pregnancy. While existing research in prenatal psychology has largely emphasized risk factors, such as stress and emotional vulnerability, limited attention has been given to proactive and reflective parental experiences. Using a qualitative phenomenological approach, this study examines how parents engage with their psychological and emotional processes during pregnancy. Data were collected using in-depth, semistructured interviews with parents who reported intentional prenatal practices. Reflexive thematic analysis following Braun and Clarke’s framework revealed five core themes: emotional preparedness, psychological agency, prenatal bonding, identity transition, and acceptance of uncertainty. Findings suggest that pregnancy can be experienced as a process of growth, rather than solely a period of vulnerability. Conscious Conception is proposed as an integrative conceptual framework for understanding intentional engagement before and during pregnancy, emphasizing emotional awareness, relational meaning-making, and adaptive coping. Implications for prenatal education and support are discussed.